2002
DOI: 10.1016/s0736-0266(02)00050-5
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of joint fluid in total knee arthroplasty patients

Abstract: While the properties ofjoint fluid may affect the tribology of joint replacement prostheses, the flow parameters of joint fluid have not yet been examined in the context of total knee arthroplasty (TKA). The objective of this study wils to evaluate the flow properties ofjoint fluids in patients undergoing index TKA or revision TKA. We hypothesized that an alteration of the properties ofjoint fluid would result from TKA. The steady-shear viscosity and storage and loss moduli were evaluated in joint fluid from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 17 publications
1
81
1
1
Order By: Relevance
“…, representative of human synovial fluid (Mazzucco et al, 2002;Walker et al, 1970), and was chosen over less-viscous bovine calf serum for that reason. To help keep the third body debris suspended, this fluid was actively circulated throughout the test by means of a peristaltic pump ( Figure 1, Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…, representative of human synovial fluid (Mazzucco et al, 2002;Walker et al, 1970), and was chosen over less-viscous bovine calf serum for that reason. To help keep the third body debris suspended, this fluid was actively circulated throughout the test by means of a peristaltic pump ( Figure 1, Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Surgical therapies mainly entail osteotomy and arthroplasty. 5 Knee OA has been associated with a decrease in the elasticity and viscosity of the synovial fluid, [6][7][8] which may alter the transmission of mechanical forces to the articular cartilage, possibly increasing its susceptibility to mechanical damage, or wear and tear. Viscosupplementation is an intra-articular therapeutic modality based on the physiological importance of hyaluronan in synovial joints.…”
Section: 注射Hylan G-f 20治療華籍患者膝關節骨性關節 炎的功效和安全性:前瞻性、縱向多中心研究mentioning
confidence: 99%
“…Studies have found that hyaluronic acid plays a key role in fluid film lubrication and the viscosity of the synovial fluid. Decreased production of HA by type B synoviocytes could explain the decreased viscosity in post arthroplasty fluid and a reciprocal increase of joint wear [37,38]. Lubricin has previously been identified as a key protein in boundary lubrication [55].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mazzucco et al [37] examined the flow properties of synovial fluid at the time of total knee arthroplasty (TKA) and at revision. Fifty-eight samples were obtained from patients undergoing index TKA surgery for osteoarthritis, 19 from revision TKA in other patients and two samples from aspirated effused joints that had undergone previous TKA.…”
Section: Synovial Fluid Propertiesmentioning
confidence: 99%